Some Asymmetry Problems of the Socio-Economic and Political Relations of Territorial Subjects of the Russian Federation - Misakov, Valery S.; Misakov, Anzor V.; Tsurova, Lisa A.; Eskiyev, Moussa A.; Ilayeva, Zarema M. (Journal of History Culture and Art Research, 2017)
In this article, the problems of territorial alignment asymmetry of the depressive republics in the North Caucasus are considered. It is proved that while making the integrated assessment for the involvement efficiency of factors into the conditions of the market relations and economic development of the region for providing set social results, it is possible to consider the level of social and economic development of the region of the Russian Federation. For these purposes it is expedient to use two complex indicators reflecting key aspects of territorial development: economic development level of the territory; social development level of the territory.